Determination of oxygen perfusion in the area of radiation-induced fibrosis of the skin in patients with breast cancer and its role in pathogenesis of late radiation injury - Agishev, T.T.; Topuzov, E.E.; Krasnozhon, D.A.; Petrachkov, A.O.; Pavlov, R.V.; Doniyarov, S.H. (Experimental Oncology, 2018)
Aim: Late radiation injury in the form of radiation-induced fibrosis (RIF) is one of the many complications of radiation therapy. The aim was to evaluate oxygen perfusion in the skin in the area of late radiation injury manifested as RIF in patients with breast cancer. Materials and Methods: Based on our first-hand experience in treating late radiation injures of soft tissues in patients with breast cancer, we measured oxygen perfusion of the skin (tсрО₂) in the area of late radiation injury using a transcutaneous monitor (oximeter) TCM 400 (Radiometer, Denmark). Results: Partial oxygen pressure tcpO₂ in the RIF area in patients with breast cancer didn’t show any significant decrease compared to healthy tissue. Mean value of partial oxygen pressure tcpO₂ in the RIF area was 42.650 ± 9.178 mmHg, in the healthy tissue it was 45.180 ± 8.025 mmHg. Maximal difference in tcpO₂ between the damaged and healthy tissue was 30 mmHg. Conclusions: Results of the study suggest that there’s no significant difference between oxygen perfusion (tcpO₂) in the area of RIF and healthy tissue. Key Words: breast cancer, late radiation injury, radiation-induced fibrosis of the skin, oxygen perfusion of the skin.